Content Analysis of Media Reports on Predator Attacks on Humans: Toward an Understanding of Human Risk Perception and Predator Acceptance. (18th July 2018) - Bombieri, Giulia; Nanni, Veronica; Delgado, María del Mar; Fedriani, José M; López-Bao, José Vicente; Pedrini, Paolo; Penteriani, Vincenzo
Abstract: Public tolerance toward predators is fundamental in their conservation and is highly driven by people's perception of the risk they may pose. Although predator attacks on humans are rare, they create lasting media attention, and the way the media covers them might affect people's risk perception. Understanding how mass media presents attacks and how this can affect perception will provide insights into potential strategies to improve coexistence with these species. We collected media reports of predator attacks on humans and examined their content. Almost half (41.5%) of the analyzed reports contained graphic elements. Differences in framing between species groups or species were found, with sharks and leopards having the highest proportion of graphic reports, whereas canids and bears had the highest number of neutral reports. This bias in coverage, instead of providing insights into the causes of these incidents and possible remedies, may provoke fear and decrease support for predator conservation.